Fungal keratitis in a mare: case report in Costa Rica - Bermúdez Jiménez, Eugenia (2020)
This paper discusses the diagnosis and clinical management of a case of equine keratomycosis. A pregnant Iberic mare was diagnosed with Aspergillus subgenus Circumdati section Circumdati, by direct microscopic examination, cytology, and fungal culture after being treated with a topical antibiotic and steroid drops in her left eye for over a month. The mare developed a melting ulcer and, as a result, topical miconazole 1% was prescribed; while being treated the iris prolapsed, and surgery was suggested but not conducted. After the treatment, the eye was not visual but in the orbit.